1998
DOI: 10.1115/1.2829328
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Decision-Based Engineering Design

Abstract: Engineering design is increasingly recognized as a decision-making process. This recognition brings with it the richness of many well-developed theories and methods from economics, operations research, decision sciences, and other disciplines. Done correctly, it forces the process of engineering design into a total systems context, and demands that design decisions account for a product’s total life cycle. It also provides a theory of design that is based on a rigorous set of axioms that underlie value theory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
302
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 524 publications
(303 citation statements)
references
References 8 publications
0
302
0
1
Order By: Relevance
“…According to standard microeconomic theory [3], improvement in product quality yields an increase in product demand q. Hazelrigg [4] observed that engineering decisions x affect product performance attributes , which in turn affect the demand of the product q, as shown in Figure 6. In our case, the surface roughness decision x for the intake manifold of engine M influences horsepower , a product characteristic observed by the consumer, and hence it would affect product demand q.…”
Section: Economic Modelingmentioning
confidence: 99%
“…According to standard microeconomic theory [3], improvement in product quality yields an increase in product demand q. Hazelrigg [4] observed that engineering decisions x affect product performance attributes , which in turn affect the demand of the product q, as shown in Figure 6. In our case, the surface roughness decision x for the intake manifold of engine M influences horsepower , a product characteristic observed by the consumer, and hence it would affect product demand q.…”
Section: Economic Modelingmentioning
confidence: 99%
“…In its classical definition, VDD postulates that engineers, when making design choices, must select the "best" design, rather than selecting the one that is most likely to meet requirements (Hazelrigg 1998). Collopy and Hollingsworth (2011) explains VDD using a cyclical view of the design process.…”
Section: Working With Value Driven Designmentioning
confidence: 99%
“…For example, in the field of AI, Gero (1990) suggests that analysis deals with the behaviour of objects, while evaluation is a comparison between alternatives. In AI, one can therefore think of analysis as the prediction of how an artefact (product, service or system) may behave according to a set of determined criteria (reliability, sustainability, costs, flexibility, feasibility, and so forth) (Gero & Kannengiesser, 2004;Hazelrigg, 1998). Evaluation, in turn, can be understood in the general field of design as the means by which one can compare alternative concepts (see, for example, how Dieter and Schmidt (2013) explain evaluation).…”
Section: Analysis and Evaluation In The Early Stages Of Designingmentioning
confidence: 99%